Self-esteem development from young adult to old age a cohort-sequential longitudinal study.[article]. - Orth, Ulrich
The authors examined the development of self-esteem from young adulthood to old age. Date came from the Americans' changing lives study, which include 4 assessments across a 16-year period of a nationally representative sample of 3,617 individuals aged 25 years to 104 years. Latent growth curve analysis indicated that self-esteem follows a quadratic trajectory across the adult life span, increasing during young and middle adulthood, reaching a peak at about 60 years, and then declining in old age. No cohort differences in the self-esteem trajectory were found. Women had lower self-esteem than did men in young adulthood, but their trajectories converged in old age. Whites and Blacks had similar trajectories in young and middle adulthood, but the self-esteem of Blacks declined more sharply in old age than did the self-esteem of Whites. More educated individuals had higher self-esteem than did less educated individuals, but their trajectories were similar. Moreover, the results suggested that changes in socioeconomic status and physical health account for the decline in self-esteem that occurs in old age.